Factors associated with mortality in severely malnourished hospitalized children who developed septic shock - Visnu Pritom Chowdhury; Monira Sarmin; Mehnaz Kamal; Shafiul Islam; Mohammad Abubakar Siddik; Farzana Afroze; Muhammad Waliur Rahman; Tahmeed Ahmed; Mohammod Jobayer Chisti (Journal of Infection in Developing Countries)
Introduction: Septic shock can often lead to death, even in resourceful settings, if not handled carefully. Therefore, we sought to evaluate the factors associated with deaths in the context of severe malnutrition and also the effects of early, i.e., within 3 hours of diagnosing septic shock vs. late blood transfusion.